DESIGN AND ANALYSIS OF NON INVERTING AND INVERTING MIXED LOGIC4-TO-16 DECODER USING MENTOR GRAPHICS 16NMTECHNOLOGY - MDTOUFEEQ AHMED (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
DESIGN AND ANALYSIS OF NON INVERTING AND INVERTING MIXED LOGIC4-TO-16 DECODER USING MENTOR GRAPHICS 16NMTECHNOLOGY